Dispersal of Mycobacterium tuberculosis Driven by Historical European Trade in the South Pacific - Mulholland, Claire V.; Shockey, Abigail C.; Aung, Htin L.; Cursons, Ray T.; O’Toole, Ronan F.; Gautam, Sanjay S.; Brites, Daniela; Gagneux, Sebastien; Roberts, Sally A.; Karalus, Noel; Cook, Gregory M.; Pepperell, Caitlin S.; et al. (Frontiers in Microbiology, 2019)
Mycobacterium tuberculosis (Mtb) is a globally distributed bacterial pathogen whose population structure has largely been shaped by the activities of its obligate human host. Oceania was the last major global region to be reached by Europeans and is the last region for which the dispersal and evolution of Mtb remains largely unexplored. Here, we investigated the evolutionary history of the Euro-American L4.4 sublineage and its dispersal to Polynesia. Using a phylodynamics approach and a dataset of 236 global Mtb L4.4 genomes we have traced the origins and dispersal of L4.4 strains to New Zealand. These strains are predominantly found in indigenous Māori and Pacific people and we identify a clade of European, likely French, origin that is prevalent in indigenous populations in both New Zealand and Canada. Molecular dating suggests the expansion of European trade networks in the early 19th century drove the dispersal of this clade to the South Pacific. We also identify historical and social factors within the region that have contributed to the local spread and expansion of these strains, including recent Pacific migrations to New Zealand and the rapid urbanization of Māori in the 20th century. Our results offer new insight into the expansion and dispersal of Mtb in the South Pacific and provide a striking example of the role of historical European migrations in the global dispersal of Mtb.